Working with the Market : Approach to Reducing Urban Slums in India - Annez, Patricia Clarke; Bertaud, Alain; Patel, Bimal; Phatak, V. K. (2012)
This paper examines the policy options for India as it seeks to improve living conditions of the poor on a large scale and reduce the population in slums. Addressing the problem requires first a diagnosis of the market at the city level and a recognition that government interventions, rather than thwarting the operations of the market, should seek to make it operate better. This can substantially reduce the subsidies required to assist low income households to attain decent living standards. The authors show that government programs that directly provide housing would cost, in conservative estimates, about of 20 to 30 percent of GDP, and cannot solve a problem on the scale of India's. Using two case studies, for Mumbai and Ahmedabad, the paper offers a critical examination of government policies that shape the real estate market and make formal housing unaffordable for a large part of the population. It illustrates how simple city level market diagnostics can be used to identify policy changes and design smaller assistance programs that can reach the poor. The linkage between chronic infrastructure backlogs and policies makes housing unnecessarily expensive. Increasing the carrying capacity of cities is essential for gaining acceptance of real estate policies suited to Indian cities. The authors propose approaches for funding major investments to achieve this.